2002
DOI: 10.1073/pnas.261708898
|View full text |Cite
|
Sign up to set email alerts
|

Feeding acetyl- l -carnitine and lipoic acid to old rats significantly improves metabolic function while decreasing oxidative stress

Abstract: Mitochondrial-supported bioenergetics decline and oxidative stress increases during aging. To address whether the dietary addition of acetyl-L-carnitine [ALCAR, 1.5% (wt͞vol) in the drinking water] and͞or (R)-␣-lipoic acid [LA, 0.5% (wt͞wt) in the chow] improved these endpoints, young (2-4 mo) and old (24 -28 mo) F344 rats were supplemented for up to 1 mo before death and hepatocyte isolation. ALCAR؉LA partially reversed the age-related decline in average mitochondrial membrane potential and significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
170
2
10

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(194 citation statements)
references
References 35 publications
12
170
2
10
Order By: Relevance
“…Additionally, acetyl L-carnitine attenuated ketamine-induced behavioral alterations and body weight decrements in preweaning rats (Boctor et al, 2008) and was found to exert efficient preventive effects in a cellular model of Parkinson's disease (Zhang et al, 2010). Beneficial effects of acetyl L-carnitine on cognitive and mitochondrial dysfunction have been shown in aging rats (Hagen et al, 2002a;Liu et al, 2002), as well. In our earlier study, we speculated that acetyl L-carnitine's reversal of ketamine-induced decrease in heart rate and ERK/MAPK activity could be mediated by calcium-modulated signaling (Kanungo et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, acetyl L-carnitine attenuated ketamine-induced behavioral alterations and body weight decrements in preweaning rats (Boctor et al, 2008) and was found to exert efficient preventive effects in a cellular model of Parkinson's disease (Zhang et al, 2010). Beneficial effects of acetyl L-carnitine on cognitive and mitochondrial dysfunction have been shown in aging rats (Hagen et al, 2002a;Liu et al, 2002), as well. In our earlier study, we speculated that acetyl L-carnitine's reversal of ketamine-induced decrease in heart rate and ERK/MAPK activity could be mediated by calcium-modulated signaling (Kanungo et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Another important property of the carnitines is their ability to neutralize toxic acyl-CoA production in the mitochondria (Stumpf et al, 1985), which correlates with numerous diseases of the CNS including neurodegenerative diseases (Makar et al, 1995;Orth and Schapira, 2002;Rubio et al, 1998). Acetyl L-carnitine is also reportedly effective in reducing age-dependent mitochondria functional decay and in restoring mitochondrial membrane potential, cardiolipin content, metabolic oxygen (O2) consumption, and β-oxidation of fatty acids (Gadaleta et al, 1998;Hagen et al, 1998Hagen et al, , 2002a. For neurons at early developmental stages, co-administration of L-carnitine significantly diminished ROS (reactive oxygen species) generation and provided near complete protection of neurons from ketamineinduced neurodegeneration .…”
Section: Introductionmentioning
confidence: 99%
“…The complementary effect of LA and ALC on cognitive and mitochondrial dysfunction has been shown in ageing rats [27,28,40]. One reason is that LA+ALC act on different pathways necessary for mitochondria: LA is a mitochondrial antioxidant and cofactor of pyruvate dehydrogenase, while ALC is an energy enhancer [25,41].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Furthermore, carnitine strongly inhibited the destruction of the mitochondrial membrane and mitochondrial dysfunction-induced injury in various types of cells. [22][23][24][25] These findings indicate that oxidative stress elicited from abnormally accumulated copper increased the amount of free fatty acids, thereby inducing mitochondrial dysfunction, resulting in cell death and enhanced secondary generation of ROS, which are significantly inhibited by carnitine treatment. Consistent with this notion is a report indicating that administration of carnitine decreased free fatty acids in serum and tissues and prevented tissue injury in juvenile visceral steatosis (JVS) mice that lack a carnitine transporter.…”
Section: Discussionmentioning
confidence: 99%
“…21 In fact, there are also several reports showing that carnitine effectively inhibited mitochondrial injury induced by oxidative stress and mitochondriadependent apoptosis. [22][23][24][25] It is thought that carnitine shows its protective effects on mitochondria and on whole cells by inhibiting free fatty acid-induced mitochondrial membrane damage and/or its secondary effects. 22,26,27 Using the hypothesis that oxidative injury induced during the process of hepatocarcinogenesis in LEC rats might be inhibited by carnitine, we investigated whether this agent could prevent inflammatory damage and hepatocarcinogenesis in LEC rats.…”
mentioning
confidence: 99%